Electromagnetic Linear Machines with Dual Halbach Array Design and Analysis - Yan, Liang; Zhang, Lu.; Peng, Juanjuan; Zhang, Lei.; Jiao, Zongxia; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book extends the conventional two-dimensional (2D) magnet arrangement into 3D pattern for permanent magnet linear machines for the first time, and proposes a novel dual Halbach array. It can not only effectively increase the radial component of magnetic flux density and output force of tubular linear machines, but also significantly reduce the axial flux density, radial force and thus system vibrations and noises. The book is also the first to address the fundamentals and provide a summary of conventional arrays, as well as novel concepts for PM pole design in electric linear machines. It covers theoretical study, numerical simulation, design optimization and experimental works systematically. The design concept and analytical approaches can be implemented to other linear and rotary machines with similar structures. The book will be of interest to academics, researchers, R&D engineers and graduate students in electronic engineering and mechanical engineering who wish to learn the core principles, methods, and applications of linear and rotary machines.
Introduction -- Working Principle and Pole Arrays -- Magnetic Field Modeling -- Mathematical Modeling of Output Force -- Mathematical Modeling of Inductance -- Comparison between Analytical Models and Finite Element Results -- Design Optimization of Linear Machines -- Prototype Development and Experiments.
Keywords: Engineering mathematics; Engineering -- Data processing; Machinery; Mathematics -- Data processing; Computer simulation; Mathematical and Computational Engineering Applications; Machinery and Machine Elements; Computational Mathematics and Numerical Analysis; Computer Modelling